Biointerface topography mediates the interplay between endothelial cells and monocytes. Issue 23 (6th April 2020) - Liu, Yan; Deng, Wenshuai; Yang, Liangliang; Fu, Xiuxiu; Wang, Zhibin; van Rijn, Patrick; Zhou, Qihui; Yu, Tao
Abstract : This study offers a new in vitro system to understand the interplay between HUVEC monolayer and monocytes mediated by aligned topographies, which may be useful for vascular repair and disease modeling for drug testing. Abstract : Endothelial cell (EC) monolayers located in the inner lining of blood vessels serve as a semipermeable barrier between circulating blood and surrounding tissues. The structure and function of the EC monolayer affect the recruitment and adhesion of monocytes, which plays a pivotal role in the development of inflammation and atherosclerosis. Here we investigate the effect of material wrinkled topographies on the responses of human umbilical vein endothelial cells (HUVECs) and adhesion of monocytes to HUVECs. It is found that HUVEC responses are non-linearly mediated by surface topographies with different dimensions. Specifically, more cell elongation and better cell orientation on the wrinkled surface with a 3.5 μm amplitude and 10 μm wavelength (W10) are observed compared to other surfaces. The proliferation rate of HUVECs on the W10 surface is higher than that on other surfaces due to more 5-ethynyl-2′-deoxyuridine (EdU) detected on the W10 surface. Also, greater expression of inflammatory cytokines from HUVECs and adhesion of monocytes to HUVECs on the W10 surface is shown than other surfaces due to greater expression of p-AKT and ICAM, respectively. This study offers a new in vitro system to understand the interplay between HUVEC monolayers and monocytes mediated by aligned topographies, which may be useful for vascular repair and disease modeling for drug testing.